USP7: Novel Drug Target in Cancer Therapy - Wang, Zhiru; Kang, Wenting; You, Yinghua; Pang, Jingru; Ren, Hongmei; Suo, Zhenhe; Liu, Hongmin; Zheng, Yichao (Frontiers in Pharmacology, 2019)
Ubiquitin specific protease 7 (USP7) is one of the deubiquitinating enzymes (DUB) that erases ubiquitin and protects substrate proteins from degradation. Full activity of USP7 requires the C-terminal Ub-like domains fold back onto the catalytic domain, allowing the remodeling of the active site to a catalytically competent state by the C-terminal peptide. Until now, numerous proteins have been identified as substrates of USP7, which play a key role in cell cycle, DNA repair, chromatin remodeling, and epigenetic regulation. Aberrant USP7 activity or expression may promote oncogenesis and viral disease, making it a target for therapeutic intervention. Currently, several synthetic small molecules have been identified as inhibitors of USP7, and applied in the treatment of diverse diseases. Hence, USP7 may be a promising therapeutic target for the treatment of cancer.